Implementasi hak asasi manusia dalam kewarganegaraan Indonesia: Tantangan dan peran pendidikan kewarganegaraan - Masudi, Nawwaf (Maliki Interdisciplinary Journal, 2026)
Human rights are inherent and fundamental rights possessed by every individual and serve as a significant indicator of democratic governance. In the Indonesian context, human rights are strongly connected to the concept of citizenship because every citizen holds constitutional rights that are required to be safeguarded by the state. This article seeks to analyze the implementation of human rights within Indonesian citizenship, identify the legal foundations governing them, and examine the role of civic education in promoting awareness of the importance of respecting human rights. The study employs a literature review method by utilizing various sources, including books, academic journals, legal regulations, and official reports issued by relevant institutions. The findings indicate that Indonesia has established a fairly comprehensive legal framework for the protection of human rights. Nevertheless, its implementation continues to encounter several obstacles, such as discrimination, intolerance, and inadequate law enforcement. Civic education has a strategic role in developing citizens who understand their rights and obligations while demonstrating tolerant, democratic, and responsible behavior. Therefore, strengthening a culture of human rights must be carried out continuously through cooperation among the government, educational institutions, and society.